Cyber Defense Using Cyber Threat Intelligence to Anticipate and Avoid Future Cyber Attacks - Eltayeb, Omer Eltayeb Omer (Journal of Ecohumanism, 2024)
Research objective: This study evaluates the efficiency of cyber threat intelligence (CTI) for predicting and mitigating cyber threats, which is important in business today. Organisations endure cyber assaults and fight cyber crimes, which threaten commercial exposure. CTI is a proactive approach to these risks since it gives the finest methods and relevant information on potential cyber crimes. Research significance: This review article analyses the literature in the context to find gaps and include ethical research practices. This systematic study may determine how threat intelligence improves cyber security knowledge and eliminates cyber threats by examining assessable information. It may guide the development of new threat intelligence-influencing methods and frameworks. Methodology: Through a qualitative approach based on the systematic review, the study goals were evaluated, analysed, and explained. PRISMA chart was also used to describe exclusion and inclusion study criteria to ensure correct data gathering. The results were presented in a thematic analysis while examining article dependability, quality, and validity. The author used inductive research to reach the primary study conclusions. Using observations or data, inductive inquiry creates hypotheses or generalisations. Research findings: Threat intelligence may considerably increase an organisation’s ability to anticipate and prevent cyber threats. The literature emphasised that threat information improves incident response, identifies new threats, and strengthens cyber security. Organisations should continually train and educate cyber security personnel to increase threat intelligence utilisation. Instruct incident response, threat intelligence analysis, and emerging threat trends.CTI helps a company grow smoothly and achieve its goals.